Spatial properties of L- and M-cone driven incremental (On-) and decremental (Off-) electroretinograms: evidence for the involvement of multiple post-receptoral mechanisms - Tsai, Tina I.; Jacob, Mellina M.; Mckeefry, Declan; Murray, Ian J.; Parry, Neil R. A.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
An overview of electroretinogram response components to incremental and decremental steps in L- and M-cone excitation was obtained in human observers, while varying the spatial properties of the stimulus. Responses to L- and M-cone stimuli of opposite polarity resembled each other, particularly within the central 35° of the retina. All amplitudes grew as stimulus size increased; however, earlier and later components of the On- and Off-responses showed differing degrees of dependency on stimulus size. Thus, they may reflect different proportions of responses originating in parvocellular (less stimulus size-dependent) and magnocellular (more stimulus size-dependent) streams.
EVALuna2:21297